Micromechanics of diffusion-induced damage evolution in reinforced polymers - Abhilash, A; Joshi, S.; Mukherjee, Abhijit; Mishnaevsky, L. (Elsevier Ltd, 2011)
In this work we numerically investigate the nucleation and evolution of micromechanical damage in reinforced glassy polymers under transient hygro-mechanical loading. In particular, we demonstrate the role that fiber distribution plays in the evolution of overall damage due to fiber-matrix interfacial debonding under moisture ingress. The heterogeneity of fiber distribution (clustering) is characterized by the coefficient of variation Cv of the center-to-center distances between interacting fibers, determined by identifying a cut-off radius around a typical fiber. The initial moisture diffusion-induced damage provides synergistic conditions for the rapid evolution of debonding under subsequent mechanical loading. The results indicate that microstructural heterogeneity strongly affects the moisture diffusion characteristics that in turn hurt the overall load carrying capacity of a composite due to aggravated damage. The strong dependence of the moisture-induced damage evolution on the fiber arrangement suggests that one should not resort to using simplistic unit cell models that assume regular fiber arrangements in such cases.